A Review and Synthesis of Entrepreneurship Research: Towards an Integrative Model of Dependent Variables. (September 2014) - Wang, Xuequn; Jessup, Leonard M.
To assess the progress of the burgeoning entrepreneurship research literature and whether the entrepreneurship research converges or diverges since Shane and Venkataraman (2000, 2001 ), we conducted a systematic review of dependent variables in the entrepreneurship literature across the US and Europe. We find that the entrepreneurship literature becomes relatively stable since 2005 and that the US and the European literature converge on seven core categories of dependent variables. We then develop an integrative model of dependent variables to summarise previous research. We conclude our study with mentioning the implications for the existing literature and future studies in the field of entrepreneurship.